Ben solved an equation as shown below, Equation 2 (-3×+1)=9×-8. what did he do wrong. step1. -6×+2=9×- 8

Question

Ben solved an equation as shown below, Equation 2 (-3×+1)=9×-8. what did he do wrong. step1. -6×+2=9×- 8. step2. -6×+9×=-8+2. step3. 3x=-6. step4. x=-2

0

Answers ( No )

    0
    2021-11-25T21:33:49+00:00

    failed to evaluate 9 × – 8

    2( – 3x + 1) = 9 × – 8

    – 6x + 2 = – 72 ( subtract 2 from both sides )

    – 6x = – 74 ( divide both sides by – 6 )

    x = \frac{-74}{-6} = \frac{37}{3}

    0
    2021-11-25T21:33:58+00:00

    He just switched sides of the variables and numbers. Instead if adding the opposite.

Leave an answer

Browse
Browse